REDUCTION OF PLUM FRUIT LOSSES DURING TREATMENT WITH SALICYLIC ACID (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The study of preserving the quality of fruit raw materials becomes relevant in connection with the value of plum fruits as a food product for dessert and technological purposes in the processing industry. Studying the influence of various methods of post-harvest processing of plum fruits will allow producers to choose the optimal method of storing fruits for a long period of time and will increase the quality of products on the modern market. The purpose of the conducted research was to study the influence of pre-treatment of plum fruits with a solution of salicylic acid on its preservation.The object of research is the technology of pre-treatment of plum fruits with salicylic acid.Pre-treatment of plum fruits with salicylic acid increases the duration of storage by 8 days. When spraying fruits with a solution of salicylic acid with a concentration of 100 mg/l, the yield of standard products was higher and amounted to 84.8% with the lowest absolute waste - respectively 4.5% and technical defect 5.9%Minimal natural losses of 4.8% after 30 days of storage of plum fruits were ensured by their treatment with a solution of salicylic acid at a concentration of 100 mg/l. Treatment of plum fruits with a solution of 100 mg/l salicylic acid made it possible to reduce absolute waste by 2.3% compared to untreated fruits. The amount of daily loss of fruit mass was uneven. Daily losses increased until the middle of the storage period (18–20 days), then slowed somewhat. More significantly, when treated with a solution of salicylic acid with a concentration of 100 mg/l. Regression analysis established a direct relationship between the duration of storage of plum fruits and daily weight loss during its storage. Equations of weight loss of fruits depending on the concentration of salicylic acid solution are given.
Keywords: plum fruits; natural losses; microbiological diseases; physiological disorders; regression model; output of marketable products